THE NEW PRAGMATISM OR THE ECONOMY OF THE FUTURE - G.W. Kolodko (Финансы: теория и практика)
How can we correlate a practical approach to the economy with an uncompromisingness and an eternal desire for change something? Is it possible to be both a pragmatist and a radical changes supporter? And is it worth doing so? Yes, it is, what is more, it is the fact that if we want to introduce something new into the economy of the future (and we certainly do), contribute to its sustainable growth and development, it is necessary to go over the whole system of values. Yet, we should not forget about pragmatism, which is a fundamental characteristic of the rational economy management. What we need is a systemic approach to understanding of the individual’s rights and duties that would contribute to the social unity and economic development.We deal with the basic principles underlying the social and economic processes with its economic goals. The most important thing here is probably the balanced and long-term development of social and economic relations.However, there are some other specific principles that should become the foundation of the practical component that identifies the vector of the political and economic strategy thought in the future. The economy is not only ascience that offers a theoretical interpretation of the rational economy management, but also a tool for changing the world for the better.The article illustrates the economy management principles, distribution of income principles and the economic agents’ interaction in the presence of constant changes in the value system. It is necessary to examine the human needs, their nature and structure, priorities and preferences in order to manage the real sector development.